Crandall Gymnasium
Caption reads: 'The Gymnasium has two separate locker rooms with modern shower rooms, basketball courts with seating for 1200, space for boxing, gymnastics, fencing, wrestling, badminton, etc. Across the street is the football field with grand-stand seating 6000 persons'